Träning och test med hund på brunbjörn (Ursus arctos) i hägn - Widegren, Ida (2020)
The main cause of adult Brown bear (Ursus arctos) mortality in Sweden is due to legal hunting and there has been a game culture for this specie since 1943. Today there is two game enclosures for brown bears located in Sweden, one in Almunge and one in Junsele. The main reason for training dogs on bears in these enclosures is to ensure bear-safe dogs both for encounters when tracking bears that been wounded due to hunting or accidents, for bear hunting and in case of bear encounters when hunting other game species in bear-tight areas. Although the ideas would be favourable for either the safety of the hunters and their dogs or the welfare of potentially injured wild bears, the welfare of the animals used in these operations must be taken into consideration.